CD38-driven NAD⁺ depletion governs crypt structure and barrier dysfunction in fluorouracil-induced colonic mucositis: From metabolic collapse to architectural remodeling - Elsayed A. Elmorsy; Rabab S. Hamad; Mohammed Alorini; Attia M. Gabr; Hamad Alsaykhan; Mostafa M. Khodeir; Mohamed F. Hindawy; Abdulaziz A. Alsalloom; Eman Mohamad El Nashar; Ahmed G. Hamad; Haytham Ali; Mohammed Ashraf Ali; et al. (Tissue and Cell, 2026)

Interrupting a mitochondrial DNA–driven innate immune circuit attenuates hepatic tissue remodeling and fibrotic architecture in experimental steatohepatitis - Rabab S. Hamad; Sura Akram Mohammed; Waseem Ali Hasan; Norhan Ahmed AbuoHashish; Sherin Refat El Afify; Mohamed A.M. Ali; Alaa Eldin Ahmed Mohamed; Attalla F. El-kott; Mohammed A. AlShehri; Kareem Morsy; Alshaimaa A. Farrag; Karem Mohamed Salem; et al. (Tissue and Cell, 2026)

STING organelle stress sensing in the liver drives hepatocyte fate and remodeling - Rabab S. Hamad; Elsayed A. Elmorsy; Fatma Elnaghy; Maha M. Amer; Mohamed R. Abdel-Hamed; Alshaimaa A. Farrag; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; Anis Ahmad Chaudhary; et al. (Tissue and Cell, 2026)

Ultrastructural organization of the neurovascular unit: Nanoscale perspectives on blood-brain barrier architecture - Rabab S. Hamad; Sameh Saber; Alshaimaa A. Farrag; Hanan Eissa; Elsayed A. Elmorsy; Attalla F. El-kott; Mohammed A. AlShehri; Eman A. Al-Shahari; Waleed Eltantawy; Mohamed A.M. Ali; Anis Ahmad Chaudhary; Ahmed Gaafar; et al. (Tissue and Cell, 2026)

Growth, Digestive Enzyme Activities, Antioxidant Properties, and Intestinal Histology of Nile Tilapia ( Oreochromis niloticus ) Fed Diets Supplemented With Garlic Nanoparticles - Sami Alaa Sami; Ashraf Y. El‐Dakar; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Mohammed F. El Basuini; Shymaa M. Shalaby; Mohamed M. Rashad; Simon J. Davies; Mohamed F. Abdel‐Aziz (New Zealand Journal of Marine and Freshwater Research, 2026)
This work may be the first of its kind to assess the effects of varying inclusion levels of garlic nanoparticles (NPsG) as feed additives on growth and physiological indices in Nile tilapia ( Oreochromis niloticus ). Garlic contains an organosulfur compound called allicin that can promote growth and strengthen the immune system by stimulating appetite and the intestinal flora, thus enhancing energy utilization. Nanotechnology provides new tools in aquaculture nutrition, including increasing the ability of fish to absorb nutrients rapidly and the effectiveness of feed additives by enhancing their bioavailability compared to their bulk form. Five concentrations of NPsG (0, 150, 300, 600, or 1200 mg/kg) were evaluated by their addition to a basal diet (30% crude protein). 225 juveniles with an initial weight of 3.92 g ± 0.42 (SE) were randomly divided into 15 cages of polyethylene. The cage had dimensions of length: width: height (100:40:60 cm) and was continuously aerated using a 2 HP air blower with air stones. After 42 days, feeding results revealed that NPsG supplementation had significant effects ( p < 0.05) on improving the performance, physiological indicators, and histomorphometry of the intestine in comparison with the control. Fish that were fed a dietary supplement of 600 mg/kg of NPsG exhibited the highest specific growth rate (2.80%/day), along with elevated levels of intestinal enzymes lipase, amylase, and proteases (212.40, 15.00, and 318.60 U/g of intestine, respectively) and the lowest malondialdehyde level (81 nmol/g of liver tissue). This group was followed by fish fed a diet of 300 mg/kg of NPsG, which did not significantly differ from those fed 600 mg/kg of NPsG in superoxide dismutase, total antioxidant capacity, and histomorphometry of intestine villi. Finally, the complete dose–response recommendation (benefit at 300–600 mg/kg and detriment at 1200).

Corrigendum to : The nano–biointerface as a structural regulator of cell behavior: Interactions of extracellular vesicles, synthetic nanocarriers, and nanofibers with cells [Tissue Cell, Vol. 101, August 2026, 103431] - Rabab S. Hamad; Sameh Saber; Alshaimaa A. Farrag; Hanan Eissa; Elsayed A. Elmorsy; Attalla F. El-kott; Mohammed A. AlShehri; Eman A. Al-Shahari; Waleed Eltantawy; Mohamed A.M. Ali; Anis Ahmad Chaudhary; Ahmed Gaafar; et al. (Tissue and Cell, 2026)

The nano–biointerface as a structural regulator of cell behavior: Interactions of extracellular vesicles, synthetic nanocarriers, and nanofibers with cells - Rabab S. Hamad; Sameh Saber; Alshaimaa A. Farrag; Hanan Eissa; Elsayed A. Elmorsy; Attalla F. El-kott; Mohammed A. AlShehri; Eman A. Al-Shahari; Waleed Eltantawy; Mohamed A.M. Ali; Anis Ahmad Chaudhary; Ahmed Gaafar; et al. (Tissue and Cell, 2026)

Seaweed Liquid Extract Improves Growth, Immunity, and Gene Expression in Nile Tilapia (Oreochromis niloticus) - Mohamed Ashour; Einar Ringø; Fawzia S. Ali; Ahmed Mamoon; Othman F. Abdelzaher; Roshmon Thomas Mathew; Abdallah Tageldein Mansour; Yousef Ahmed Alkhamis; Elsayed S. I. Mohammed; Hesham S. Hassanien; Mohamed A. Elokaby; Mohamed M. Mabrouk (Journal of Applied Phycology, 2026)

Retraction Note: COVID-19: pathogenesis, advances in treatment and vaccine development and environmental impact—an updated review - Youssef A. Attia; Mohamed T. El-Saadony; Ayman A. Swelum; Shaza Y. A. Qattan; Adel D. Al-qurashi; Khalid A. Asiry; Manal E. Shafi; Ahmed R. Elbestawy; Ahmed R. Gado; Asmaa F. Khafaga; Elsayed O. S. Hussein; Hani Ba-Awadh; et al. (Environmental Science and Pollution Research, 2026)

Corrigendum to “Photocatalytic degradation of reactive blue 19 and antibacterial efficacy utilizing a magnetically separable C-doped TiO₂/copper-lead ferrite nanocomposite” [J. Water Process Eng. 82 (2026) 1–15 (109535)] - Doaa F. Baamer; Elsayed T. Helmy; H.G. Mohamedbakr; Amr.M. Elbasiony; Mohamed Mokhtar M. Mostafa (Journal of Water Process Engineering, 2026)

Adenosine A₂A receptor as a dual-acting molecular switch: Glial morphological changes and neurovascular tissue remodeling in neuroinflammation and neurodegeneration - Heba Ibrahim Abd El-Moaty; Ahmed Sameh; Sameh Saber; Rabab S. Hamad; Elsayed A. Elmorsy; Norah Suliman Alsoqih; Alshaimaa A. Farrag; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; et al. (Tissue and Cell, 2026)

FOXO3a-mediated structural and cellular remodeling in liver tissue: Implications for apoptosis and homeostasis - Heba Ibrahim Abd El-Moaty; Sameh Saber; Rabab S. Hamad; Elsayed A. Elmorsy; Alshaimaa A. Farrag; Simona Cavalu; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; Waseem Ali Hasan; et al. (Tissue and Cell, 2026)

Mitigating the impact of salinity and/or bisphenol A stress on the performance of the tomato crop by spraying with an algal extract of Ascophyllum nodosum L. - Mahmoud S. Abdelmoneim; Mohamed A. Ghazy; Elsayed E. Hafez; Sherif F. Hammad; Mona F.A. Dawood (Journal of Hazardous Materials, 2026)

Toward Eco-Friendly Solutions for Plastic Pollution: Insights into Polyethylene Biodegradation - Alaa F. Elsayed; Dina H. Amin; Hassan M. Gebreel; Ihsan Mahasneh; HebatAllah I. Youssef (Water, Air, & Soil Pollution, 2026)

Molecularly diverse lonazolac-inspired pyrazole-cyanopyridin-2-one conjugates: design, synthesis, in vitro, in vivo and in silico studies as multi-target anti-inflammatory agents - Marwa A. Aziz; Azizah M. Malebari; Tarek S. Ibrahim; Mohamed F. Radwan; Deiaa E. Elsayed Abouzed; Rasha M. Allam; Majed Alharbi; Ahdab N. Khayyat; Gamal El-Din A. Abuo-Rahma; Mamdouh F. A. Mohamed (Molecular Diversity, 2026)

Sustainable valorization of unutilized marigold flowers for eco-friendly herbal gulal production and its storability effects on quality attributes - Anshul Kumar; Bharati Kashyap; Sita Ram Dhiman; Anjali Chauhan; Bhavya Bhargav; Nitin Sharma; Sabhya Pathania; Pamita Bhandari; Abeer Hashem; Graciela Dolores Avila-Quezada; Khalid F. Almutairi; Elsayed Fathi Abd_Allah (Waste Management, 2026)

A new cadinane-type sesquiterpenoid glucoside from Centaurea alexandrina - Ibrahim A. Saleh; Wael M. Elsayed; Taha A. Hussien; Abdelsamed I. Elshamy; Tarik A. Mohamed; Mohamed-Elamir F. Hegazy (Natural Product Research, 2026)

Optimizing Domestic Wastewater Treatment Using Moringa Oleifera Lam. Vegetated Constructed Wetlands: A Case Study et al.-Habil Wastewater Treatment Plant, Luxor - Naira Meky; Raouf Hassan; Mohamed F. Soliman; Aml Mahmoud; Mahmoud Elsayed (Water, Air, & Soil Pollution, 2026)

Drought Tolerance Strategies of Faba Bean Cultivars: Integrated Morphological, Physiological, and Biochemical Responses - Abdelsalam A. Shehab; Ahmed M. Abdelghany; Asmaa Hamoda; Elsayed Sh. Alwakel; Alsayed S. Farouk; Mohamed Ebaid; Sobhi F. Lamlom; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2026)
Water deficit stress significantly threatens faba bean productivity, highlighting the need to understand cultivar-specific drought tolerance mechanisms to improve breeding efforts. This study aimed to assess the morphological, physiological, and biochemical responses of three faba bean cultivars exposed to different drought levels during the vegetative and flowering stages. Three cultivars (Qidou2, Chenghu10, and Qinghai13) were subjected to different drought levels (35%, 55%, and 100% field capacity) during vegetative and blooming stages. Growth traits, root architecture, gas exchange, antioxidant enzyme activity, cuticular wax composition, and reproductive performance were systematically assessed. Different cultivars showed distinct tolerance patterns. Qidou2 had superior root growth, the highest water-use efficiency at 15.5 µmol CO₂ mmol⁻¹ H₂O, and a flower production tolerance index of about 2.0, indicating strong reproductive resilience. Chenghu10 demonstrated notable adaptability, including a 134% increase in relative intrinsic water-use efficiency under stress and elevated catalase activity at 405.75 U g⁻¹ min⁻¹. Qinghai13 showed moderate tolerance, maintaining steady photosynthesis at 10.33 µmol CO₂ m⁻² s⁻¹ and consistent enzyme activity. Cuticular wax deposition increased sharply during seedling stress (Qidou2: 6.464 to 9.845 µg cm⁻²). Reproductive traits were most stress-sensitive; for example, Qidou2 did not produce pods under severe drought despite vigorous growth. Overall, the findings highlight that coordinated responses across root architecture, physiology, metabolism, and protective barriers underpin drought adaptation. The diverse strategies identified across cultivars, from conservative water use to enhanced metabolic efficiency, provide valuable targets for breeding drought-resilient faba beans.

Photocatalytic degradation of reactive blue 19 and antibacterial efficacy utilizing a magnetically separable C-doped TiO₂/copper-lead ferrite nanocomposite - Doaa F. Baamer; Elsayed T. Helmy; H.G. Mohamed Bakr; Amr.M. Elbasiony; Mohamed Mokhtar M. Mostafa (Journal of Water Process Engineering, 2026)

Adaptive morphological and physiological strategies of Sporobolus ioclados in desert ecosystem - Muhammad Akram; Nargis Naz; Ummar Iqbal; Syeda Refat Sultana; Fahim Arshad; Muhammad Waheed; Muhammad Adeel Ghafar; Hafiz Muhammad Mohsin Hassan; Arslan Asghar; Abeer Hashem; Dalal Saad Alharbi; Graciela Dolores Avila-Quezada; et al. (The Science of Nature, 2026)

Determination of the Chemical Profile of Hibiscus rosa-sinensis L. Leaves Using Different Solvents and Evaluation of their Antioxidant, Antimitotic, and Antiproliferative Potentials - Sehrish Sadia; Muhammad Waheed; Tahira Rashid; Murad Muhammad; Huma Bashir; Fahim Arshad; Muhammad Iqbal; Abeer Hashem; Khalid F. Almutairi; Elsayed Fathi Abd-Allah (Journal of Pharmaceutical Innovation, 2026)

Scouting the Efficacy of Chitosan-coated Litsea Lipid Carriers Nanoplatform as an Oral Delivery System of Lornoxicam in an Inflammatory Animal Model - Walaa A. El-Dakroury; Abdelrahman R. Said; Gihan F. Asaad; Heba M. I. Abdallah; Marwa E. Shabana; Rahma A. Abdelsalam; Eman M. Elsadek; Basma H. Mohamed; Yara S. Mohamed; Sara M. Seliem; Elsayed Y. Hamada; Belal W. Attef; et al. (Journal of Pharmaceutical Innovation, 2026)
Lornoxicam-loaded chitosan-coated Litsea lipid nanocarriers (LRX-CS-LLCs) were developed as an innovative oral delivery system, combining the synergistic anti-inflammatory effects of Litsea cubeba oil with the mucoadhesive properties of chitosan. The GC/MS analysis of Litsea cubeba oil identified α -citral (47.56%), β -citral (26.86%), and D -limonene (14.00%). Various LRX-loaded LLCs were prepared and optimized. Fourier transform-infrared (FTIR) and differential scanning calorimetry (DSC) confirmed its structural integrity. The optimized (LRX-CS-LLCs) exhibited a particle size of 165.4 ± 6.3 nm, zeta potential of + 26.3 ± 3.2 mV, and entrapment effectiveness of 98.2%. In vitro release followed a controlled kinetic profile. In vivo, LRX-CS-LLCs significantly reduced carrageenan-induced paw edema (77 ± 1.86% inhibition) and PGE2, COX-2, and TNF-α levels by 4.4-, 3.6-, and 3-fold, respectively, compared to the positive control group. Histopathological examinations confirmed normal tissue architecture. Notably, LRX-CS-LLCs outperformed pure-LRX, marketed-LRX, and uncoated-LRX-LLCs, emphasizing its promise as an effective oral therapeutic approach for enhanced management of inflammatory conditions.

Arbuscular mycorrhizal fungi confers resistance to Macrophomina phaseolina in coriander under different nitrogen fertilizer rates - Marzouk R. Abdel-Latif; Abdelrazek S. Abdelrhim; Ranya M. S. El-Ashmony; Yasmin M. R. Abdellatif; Hanaa A. H. Armanious; Ismail A. A. Tantawy; Mahmoud Elsayed; Abeer S. Alqurashi; Hatim M. Al-Yasi; Esmat F. Ali; Abdelmonim Ali Ahmad (Journal of Plant Pathology, 2026)

Chitosan reduces methane emissions and alters the phylogenetic affiliation of sampled methanogens in in vitro rumen fermentation - Marwa F. A. Attia; Amr E. El-Nile; Alaa M. A. Gad; Mohamed S. Moharam; Ahmed E. Kholif; Raed A. Aburawash; Elsayed E. Hafez; Sobhy M. A. Sallam (Environmental Science and Pollution Research, 2026)

Zero Liquid Discharge Performance in Complex Fertilizer Industry Wastewater Treatment - Mahmoud Elsayed; Abdelrahim M. Abdeldaim; Mohamed F. Soliman; Raouf Hassan; Naira Meky (Water, Air, & Soil Pollution, 2026)

Cardioprotective effects of ghrelin and Wharton’s jelly-derived mesenchymal stem cells, alone and in combination, in doxorubicin-induced myocardial injury in rats - Amy F. Boushra; Christina Sabry Yacoub; Hamed Mohamed Osman; Amani M. El Amin Ali; Azza Mohamed Elamir; Asmaa Mohamed Elsayed; Sarah Mahmoud Gamal (Journal of Molecular Histology, 2025)

"Molecular Characterization of Extended Spectrum Beta-Lactamase Resistance in Pediatric Shigella Isolates in Egypt" - Dina F. Badr; Maysaa El Sayed Zaki; Ahmed Gomaa Elsayed; Mona Abdellatif Elsayed; Nesreen Mostafa Kamel; Mohamed Mofreh Mohamed Salam (Biochemical Genetics, 2025)

Electrolyzed water as a microbial control measure for white soft cheese - Salwa M. Awad; Eman F. Abdel-latif; Khalid Sh Tolba; Huda Elsayed; Zeinab I. Ali; Adel M. Saudi (International Dairy Journal, 2025)

Promising Alginate-Gelatin Scaffolds Containing 5-Fluorouracil and Reinforced with Zinc-Modified Hydroxyapatite: Cell Attachment and One-Year Stability Study - Ebtesam W. Elsayed; Maha F. Emam; Ahmed A. El-Ashmawy; Gehan T. El-Bassyouni; Sahar M. Mousa; Ahmed A. F. Soliman; M. El-Manawaty; Laila H. Emara (Journal of Pharmaceutical Innovation, 2025)
Purpose The current study evaluated the cell attachment capability and long-term stability of 5 - fluorouracil (5-FU) loaded alginate-gelatin scaffolds reinforced with zinc-doped hydroxyapatite (Zn-HA). Methods Zn-HA (2% and 6% Zn) was prepared and evaluated for the crystalline nature, chemical structure, and microstructure of hydroxyapatite (HA). Blank and 5-FU loaded alginate-gelatin-Zn-HA scaffolds were prepared and evaluated in terms of surface area, pore size, pore volume, and morphology using the gas adsorption technique and scanning electron microscopy (SEM). Cell attachment studies were also carried out on normal human cell line. The scaffolds were stored for one year at room temperature and evaluated for any changes in their physico-chemical properties as well as 5-FU release profile. Results The results showed that increasing zinc content decreased HA particle size. The blank scaffolds showed higher surface area, pore volume values, and a less porous structure compared to the drug-loaded ones. The pore size increased after scaffolds soaking in cell-line medium due to the hydrogel-forming materials' biodegradability and drug release. Cell growth on the presoaked drug-loaded scaffolds was improved compared to blank scaffold. XRD, FTIR and 5-FU release profile indicated that the stored scaffolds did not show any physical or chemical changes. Conclusion The prepared scaffolds showed promising results regarding cell attachment capability and long-term stability.

Green Solutions for Heavy Metal Pollution in the Aquatic Environment of the Nile Islands: Cues from some Submerged and Emergent Macrophytes - Abdel Rahman Nadi; Elsayed Mohamed; Ahmed M. M. A. Kasem; Abd El-Mageed F. M. Ghanem; Mohamed O. Badry (Water, Air, & Soil Pollution, 2025)
The study evaluates the phytoremediation potential of five wild macrophytes ‒ Setaria geminata (Forssk.) Veldkamp, Ceratophyllum demersum L., Myriophyllum spicatum L., Persicaria senegalensis (Meisn.) Soják, and Ludwigia adscendens subsp. diffusa (Forssk.) P.H. Raven‒ for iron (Fe), manganese (Mn), copper (Cu), and zinc (Zn) on the shore of two islands in Luxor governorate, Egypt: Armant (sites 1 and 2) and Aqalata (site 3). The study aimed to assess how site, season, and species influence heavy metal accumulation in plant organs, chlorophyll content, and antioxidant compounds; to evaluate phytoremediation efficiency using bioaccumulation factors; and to explore the relationship between heavy metals concentrations in shoots and the behavior of chlorophyll and antioxidants. Heavy metal concentrations in water at all three sites fell within the safe irrigation limits. However, Cu and Mn levels in sediments exceeded global freshwater recommendations during summer. Fe and Mn levels in submerged species ( C. demersum and M. spicatum ) and emergent species'belowground tissues ( S. geminata , P. senegalensis , and L. adscendens ) surpassed the permissable limits in most seasons. In contrast, Zn levels in all studied species remained within the acceptable limits, while Cu levels in S. geminata and P. senegalensis roots exceeded the permissible limits during spring and summer, respectively. The bioaccumulation factors (BAFs) for submerged species exceeded one for all metals, whereas emergent species showed BAFs greater than one only for Mn. Translocation factors (TFs) for all metals were less than one, except for Zn in P. senegalensis and L. adscendens . Chlorophyll pigments in S. geminata, M. spicatum and L. adscendens negatively correlated with most heavy metals in shoots, while a positive correlation was observed in C. demersum . Also, heavy metals in shoots negatively correlated with total phenolics and flavonoids, carotenoids and phenolics, and phenolics in C. demersum , M. spicatum and S. geminate , respectively. In contrast, L. adscendens exhibited a positive correlation between most of these elements and antioxidant compounds. The differential relationships between the studied heavy metals in shoots and chlorophyll/antioxidant compounds suggest species-specific energy allocation strategies. Our results highlight the potential of these species for phytoremediation in contaminated aquatic ecosystems, and indicate that submerged species are suitable for hyperaccumulation, while emergent macrophytes function as accumulators for Mn and excluders for Fe, Cu, and Zn.

Dietary intervention of ginger and black seed oils boosted hematology, biochemical profile, and antioxidant-immune responses in Oreochromis niloticus challenged with Aeromonas veronii - Shaimaa E. Ibrahim; Fatma M. Abdelhamid; Elsayed Nabeeh Abou ElGheit; Mohamed A.H. El-kady; Gehad E. Elshopakey; Engy F. Risha (Aquaculture, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Ameliorative potential of Populus alba leaf powder against hexaflumuron exposure in Nile tilapia: immune-antioxidant, biochemical, histological, and transcriptomic analysis - Rowida E. Ibrahim; Mohamed F. M. Farag; Mohammed S. Sobh; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Shefaa M. Bazeed; Aya Elgamal; Tarek Khamis; Simon J. Davies; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2025)

Vinpocetine and Lactobacillus Attenuated Rotenone-Induced Parkinson’s Disease and Restored Dopamine Synthesis in Rats through Modulation of Oxidative Stress, Neuroinflammation, and Lewy Bodies Inclusion - Hanan M. Hassan; Hadeer O. Abou-Hany; Ahmed Shata; Doaa Hellal; Ahmed M. El-Baz; Zeinab H. ElSaid; Amira A. Haleem; Nesreen Elsayed Morsy; Rawan M. Abozied; Bassant M. Elbrolosy; Sally Negm; Attalla F. El-kott; et al. (Journal of Neuroimmune Pharmacology, 2025)

The Combination Between Super Absorbent Polymers (SAPs) and Biofertilizers Could be an Ecofriendly Approach for Soil Chemical Properties Improving and Sustainable Wheat (Triticum Sativum) Production in Sandy Loam Soil - Osama I. A. Negim; Moustafa H. A. Moharam; Elsayed F. Elsayed; Fatma N. Thabit (Journal of Soil Science and Plant Nutrition, 2024)
Sustainable agriculture aims to provide food needs while improving soil health and protecting it from degradation and contamination from excessive chemical fertilizer use. Sandy-textured soils have low fertility and water-holding capacity. This study assessed the integrated impact of super absorbent polymers (SAPs) and biofertilizer application on the soil chemical characteristics and wheat growth parameters in sandy loam soil. Two super absorbent polymers (SAPs) included Barbary plant G3 (P1) and Aqua Gool polymer (P2), and four microbial inoculations ( Trichoderma harzianum (T), Actinomycetes ( Streptomyces rochei and Streptomyces atrovirens) (AC1 and AC2), and Bacillus subtilis (B)) as biofertilizers were used in our pot experiment. The SAPs were applied to soil at a level of 0.2% (w/w), while biofertilizers were applied in the form of microbial cell suspensions (50 ml per pot) in addition to treating wheat seed with these suspensions during cultivation. Wheat plants were irrigated every 8 days to field capacity level. Amending soil with super absorbent polymers and microbes either individually or in combination significantly reduced pH and EC, increased organic matter level, and the availability of macro- and micronutrients in soil. Wheat growth metrics, including shoot length, tiller number, biomass accumulation, leaf area, and grain yield, exhibited considerable enhancements relative to the plants of the control treatment. The interaction between P1 polymer and Streptomyces atrovirens (AC2) showed the highest performance in improving the almost studied parameters. The application of SAPs with microbial biofertilizers offers a promising eco-friendly method for enhancing soil health and wheat yield.

Influence of a mixture of oligosaccharides and β-glucan on growth performance, feed efficacy, body composition, biochemical indices, combating Streptococcus iniae infection, and gene expression of Nile tilapia (Oreochromis niloticus) - El-Sayed Hemdan Eissa; Ekemini Moses Okon; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Mohammad Bodrul Munir; Hoda A. Eissa; Sara F. Ghanem; Heba H. Mahboub; Nadia A. Abd Elghany; Hagar Sedeek Dighiesh; Moaheda E. H. Eissa; Yasmin M. Abd El-Aziz (Aquaculture International, 2024)

Effects of dietary commercial phytobiotic “Sanacore® GM” on Pacific white shrimp (Litopenaeus vannamei) growth, immune response, redux status, intestinal health, and disease resistance against Fusarium solani - El-Sayed Hemdan Eissa; Samia Elbahnaswy; Amira Hussein El-Baz; Ehab El-Haroun; Mohamed Ashour; Abdallah Tageldein Mansour; Saadea Saadony; Adel F. El-Saeed; Hoda Kabary; Samyah D. Jastaniah; Bothaina A. Alaidaroos; Manal E. Shafi; et al. (Aquaculture International, 2024)
The use of phytobiotic as functional feed additives is a promising inducer for growth performance and immune response in the Pacific whiteleg shrimp ( Litopenaeus vannamei ). It can be also commercially applied in combination with chemotherapeutic agents and vaccines. This study was carried out to evaluate the use of a commercial phytobiotic feed additive, Sanacore® GM, containing vegetable fatty acids and inactivated Saccharomyces cerevisiae with herbal extracts , on growth, body composition, non-specific immune response, antioxidant index, intestinal microflora count, and fungal resistance to Fusarium solani challenge in Pacific white shrimp, Litopenaeus vannamei . Shrimp juveniles (5.00 ± 0.1 g) were randomly distributed into 12 hapas (1 m 3 ) in triplicates at a stocking density of 20 shrimp per hapa and fed increasing levels of Sanacore® (0, 0.1, 0.2, and 0.3%) for 63 days. At the end of the feeding trial, the experimental shrimp were infected with F. solani , and mortality was recorded for 15 days. Results revealed that growth performance, feed utilization, and whole-body protein deposition were improved with increasing dietary sanacore levels. A significant improvement was reported in cellular (hemocyte counts, phagocytosis, phagocytic index, respiratory burst activity) and humoral (lysozyme and phenoloxidase) immune responses with higher dietary sanacore levels. Superoxide dismutase, catalase, and glutathione peroxidase were notably improved in shrimp-fed sanacore-supplemented diets. Meanwhile, malondialdehyde level was significantly decreased in all sanacore-supplemented shrimp. Furthermore, the dietary sanacore consistently increased probiotic bacterial counts and decreased enteric and Clostridium sp. counts in the intestine. Juveniles fed with Sanacore exhibited significantly lower mortality rates when challenged with F. solani . In conclusion, dietary sanacore could exhibit a profitable effect on the growth performance, antioxidant capacity, immunity, intestinal microbial, and the health condition of L. vannamei . Thus, sanacore can be used as an attractive feed supplement in the L. vannamei diet (0.2–0.3%), providing more insights into its application in aquaculture as a functional immunostimulant feed additive.

Adsorption behavior of Mo(VI) from aqueous solutions using tungstate-modified magnetic nanoparticle - Elsayed M. Abu Elgoud; Ahmed I. Abd-Elhamid; Hisham F. Aly (Environmental Science and Pollution Research, 2024)
A new magnetic nanoparticle modified with sodium tungstate (Mnp-Si-W) was synthesized and employed for the sorption of molybdenum from aqueous solutions. The prepared nanoparticles (Mnp-Si-W) were characterized by different advanced techniques. Different parameters that influenced the adsorption percent of Mo(VI) were investigated using a batch process. Based on a systematic investigation of the adsorption isotherms and kinetics models, Mo(VI) adsorption follows the Langmuir model and pseudo-second-order kinetics. According to the Langmuir isotherm model, the Mnp-Si-W nanoparticles exhibited a maximum adsorption capacity of 182.03 mg g −1 for Mo(VI) at pH 2.0. The effect of competing ions showed that the prepared nanoparticles have a high selectivity for the sorption of molybdenum. Moreover, the effect of some interfering anions on Mo(VI) ion sorption is found in the following order: phosphate < sulfate < chromate. Finally, the nanoparticle (Mnp-Si-W) can be successfully reused five times.

Synthesis of Nano-silica Oxide for Heavy Metal Decontamination from Aqueous Solutions - Naira Meky; Eslam Salama; Mohamed F. Soliman; Soheair G. Naeem; Mona Ossman; Mahmoud Elsayed (Water, Air, & Soil Pollution, 2024)
In the current study, nano-silica oxide (nano-SiO 2 ) was fabricated via the sol-gel technique. Then, the prepared nano-SiO 2 was characterized using X-ray diffractometer (XRD), transmission electron microscopy (TEM) coupled with energy-dispersive X-ray spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and Brunauer-Emmett-Teller (BET) specific surface area analysis. Furthermore, the fabricated nano-SiO 2 was applied for the adsorption of lead Pb (II) and chromium Cr (VI) from aqueous solutions. Additionally, the influence of different operating factors such as contact time (0–180 min), initial pH (1–11), nano-SiO 2 dose (0.1–8 g L −1 ), initial metal ion concentration (5–100 mg L −1 ), and the temperature (30–85 °C) was investigated. The nano-SiO 2 doses of 0.5 and 1 g L −1 were selected as the optimal adsorbent dose for the removal of Pb (II) and Cr (VI), respectively. These doses achieved a removal efficiency of 82.3% and 78.5% for Pb (II) and Cr (VI), after 60 and 90 min, at initial pH values of 5 and 2, respectively, using 10 mg L −1 initial metal concentration, and at room temperature. Lastly, kinetic and equilibrium studies were competently fitted using the pseudo-second-order and Freundlich models, respectively. Adsorption thermodynamic studies designate the spontaneous and thermodynamic nature of the adsorption process. These results reveal the efficiency of the fabricated nano-SiO 2 as an adsorbent for heavy metal removal from aqueous solutions. Graphical Abstract

Aridity creates global thresholds in soil nitrogen retention and availability - Ahmed S. Elrys; Mohamed F. Abo El‐Maati; Xiaoqian Dan; YuHong Wen; Jinxia Mou; Ahmed Elsayed Abdelghany; Yves Uwiragiye; Tang Shuirong; Wu Yanzheng; Lei Meng; JinBo Zhang; Christoph Müller (Global Change Biology, 2024)
Identifying tipping points in the relationship between aridity and gross nitrogen (N) cycling rates could show critical vulnerabilities of terrestrial ecosystems to climate change. Yet, the global pattern of gross N cycling response to aridity across terrestrial ecosystems remains unknown. Here, we collected 14,144 observations from 451 15 N‐labeled studies and used segmented regression to identify the global threshold responses of soil gross N cycling rates and soil process‐related variables to aridity index (AI), which decreases as aridity increases. We found on a global scale that increasing aridity reduced soil gross nitrate consumption but increased soil nitrification capacity, mainly due to reduced soil microbial biomass carbon (MBC) and N (MBN) and increased soil pH. Threshold response of gross N production and retention to aridity was observed across terrestrial ecosystems. In croplands, gross nitrification and extractable nitrate were inhibited with increasing aridity below the threshold AI ~0.8–0.9 due to inhibited ammonia‐oxidizing archaea and bacteria, while the opposite was favored above this threshold. In grasslands, gross N mineralization and immobilization decreased with increasing aridity below the threshold AI ~0.5 due to decreased MBN, but the opposite was true above this threshold. In forests, increased aridity stimulated nitrate immobilization below the threshold AI ~1.0 due to increased soil C/N ratio, but inhibited ammonium immobilization above the threshold AI ~1.3 due to decreased soil total N and increased MBC/MBN ratio. Soil dissimilatory nitrate reduction to ammonium decreased with increasing aridity globally and in forests when the threshold AI ~1.4 was passed. Overall, we suggest that any projected increase in aridity in response to climate change is likely to reduce plant N availability in arid regions while enhancing it in humid regions, affecting the provision of ecosystem services and functions.

Antitumor effect of trimetazidine in a model of solid Ehrlich carcinoma is mediated by inhibition of glycolytic pathway and AKT signaling - Reem M. Hazem; Rasha F. Aboslema; Eman T. Mehanna; Safaa M. Kishk; Mohammed Elsayed; Norhan M. El-Sayed (Chemico-Biological Interactions, 2023)

An overview of 2D metal sulfides and carbides as Na host materials for Na-ion batteries - Javed Rehman; Shiru Lin; Mehwish K. Butt; Xiaofeng Fan; Tamer Khattab; Khaled A. Elsayed; Mohamed F. Shibl (Chemical Engineering Journal, 2023)

Soil and foliar applications of zinc sulfate and iron sulfate alleviate the destructive impacts of drought stress in wheat - Md. Abdul Mannan; Mahmuda Akter Tithi; M. Rafiqul Islam; Md. Abdullah Al Mamun; Shamim Mia; Md. Zillur Rahman; Mohamed F. Awad; Abdelaleim I. ElSayed; Elsayed Mansour; Md. Sazzad Hossain (Cereal Research Communications, 2022)

Evaluation of the antineoplastic property of prodigiosins and 5-fluorouracil in restraining the growth of Ehrlich solid tumors in mice - Elsayed S. E. Hassan; Medhat W. Shafaa; Ahmed H. I. Faraag; Ehab Essawy; Ashraf A. Bakkar; Wafa A. AL-Megrin; Manal F. El-Khadragy; Mohamed S. Abdelfattah; Ahmed E. Abdel Moneim (Environmental Science and Pollution Research, 2022)

Effects of dietary supplementation of chromium methionine chelate on growth performance, oxidative stress, hematological indices, and carcass traits of broiler chickens - Ibrahim M. I. Youssef; Ibrahim M. I. Abdo; Hassan F. A. Elsukkary; Magdy F. El-Kady; Magdy Elsayed (Tropical Animal Health and Production, 2022)
This study was conducted to evaluate the dietary effects of chromium methionine (Cr-Meth) chelate on growth performance, oxidative stress parameters, blood biochemistry, and carcass traits of broiler chickens. An experiment was conducted on 34,000 1-day-old straight-run broiler chicks (Indian River; 42.0 ± 0.03) at a commercial farm. The chicks were divided randomly into 3 groups; the first group contained 17,000 birds, which used as a control, whereas the second and third groups consisted of 7000 and 10,000 birds, respectively, with 5 replicates per group. A completely randomized design was used. The birds were fed the experimental diets containing graded levels of Cr-Meth chelate: 0 (control), 50, and 100 g/ton. This compound consisted of chromium (0.4%) chelated with methionine, and it supply the diets with 200 and 400 ppb Cr for the used levels of 50 and 100 g/ton feed, respectively. Growth performance indices (body weight, body weight gain, feed intake, and feed conversion ratio) were measured throughout the experiment. At the end of experiment, 10 birds per treatment were slaughtered, and the carcass yield with relative weight of the internal organs was determined. Also, blood samples were taken and analyzed for glutathione peroxidase activity, malondialdehyde, ALT, AST, total protein, albumin, glucose, urea, creatinine, triglycerides, and total cholesterol. It was found that Cr-Meth improved the body weight, weight gain, feed intake, and feed conversion ratio of broilers. Moreover, it reduced the mortality rate of birds. The chelated chromium can alleviate the oxidative status of birds by increasing the plasma glutathione peroxidase activity and reducing the serum malondialdehyde level. It was observed that the effects of 100 g/ton Cr-Meth chelate on performance indices, mortality rate, and oxidative stress parameters were better than that of 50 g/ton inclusion rate. Supplementation of Cr-Meth increased the total protein level, but reduced the glucose, total cholesterol, and triglyceride concentrations in the blood serum. In addition, it increased the carcass yield and reduced the abdominal fat percentage of the birds’ carcass. Therefore, chromium can be included in diets of broilers at a rate of 200 to 400 ppb, and the higher concentration was more effective than the lower one. So, it can be recommended to use Cr-Meth chelate in broiler diets at 100 g/ton to improve the productive performance and reduce the oxidative stress of birds.

Ameliorative effect of flavocoxid on cyclophosphamide-induced cardio and neurotoxicity via targeting the GM-CSF/NF-κB signaling pathway - Fatma F. Elsayed; Waad M. Elshenawy; Eman M. Khalifa; Mohamed R. Rizq; Rania R. Abdelaziz (Environmental Science and Pollution Research, 2022)
Cyclophosphamide (Cyclo) is a chemotherapeutic agent used as an immunosuppressant and as a treatment for many cancerous diseases. Many previous pieces of literature proved the marked cardio and neurotoxicity of the drug. Thus, this research provides evidence on the alleviative effect of flavocoxid on the cardiac and brain toxicity of cyclophosphamide in mice and determines its underlying mechanisms. Flavocoxid (Flavo) is a potent antioxidant and anti-inflammatory agent that inhibits the peroxidase activity of cyclooxygenase (COX-1 and COX-2) enzymes and 5-lipooxygenase ( 5-LOX ). Flavo was administered orally (20 mg/kg) for 2 weeks, followed by Cyclo (100 mg/kg, i.p.) on day 14. Higher heart and brain weight indices, serum lactate dehydrogenase (LDH), creatine kinase (CK-MB), and nitric oxide (NO) were mitigated following Flavo administration. Flavo modulated oxidative stress biomarkers (malonaldehyde (MDA), glutathione (GSH), and superoxide dismutase (SOD)), tumor necrosis factor-α (TNF - α), and interleukin (IL)-1β. Additionally, cardiac troponin I (cTn-I), nuclear factor kappa B (NF-κB), brain amyloid precursor protein (APP), and granulocyte macrophage colony-stimulating factor (GM-CSF) were decreased by Flavo administration. Moreover, Flavo ameliorated heart and brain histopathological changes and caspase-3 levels. Collectively, Flavo (20 mg/kg) for 14 days showed significant cardio and neuroprotective effects due to its antioxidant, anti-inflammatory, and antiapoptotic activities via modulation of oxidative stress, inflammation, and the GM-CSF/NF-κB signaling pathway.

Characterization and Expression Analysis of Extradiol and Intradiol Dioxygenase of Phenol-Degrading Haloalkaliphilic Bacterial Isolates - Nasser H. Abbas; Afaf Elsayed; Hamdy A. Hassan; Sabha El-Sabbagh; Ashraf F. Elbaz; Hany Khalil (Current Microbiology, 2022)
Haloalkophilic bacteria have a potential advantage as a bioremediation organism of high oil-polluted and industrial wastewater. In the current study, Haloalkaliphilic isolates were obtained from Hamralake, Wadi EL-Natrun, Egypt. The phenotype script, biochemical characters, and sequence analysis of bacterial-16S rRNA were used to identify the bacterial isolates; Halomonas HA1 and Marinobacter HA2 . These strains required high concentrations of NaCl to ensure bacterial growth, especially Halomonas HA1 strain. Notably, both isolates can degrade phenol at optimal pH values, between 8 and 9, with the ability to grow in pH levels up to 11, like what was seen in the Halomonas HA1 strain. Moreover, both isolates represent two different mechanistic pathways for phenol degradation. Halomonas HA1 exploits the 1,2 phenol meta-cleavage pathway, while Marinobacter HA2 uses the 2,3 ortho-cleavage pathway as indicated by universal primers for 1,2 and 2,3 CTD genes. Interestingly, Marinobacter HA2 isolate eliminated the added phenol within an incubation period of 72 h, while the Halomonas HA1 isolate invested 96 h in degrading 84% of the same amount of phenol. Phylogenetic analysis of these 1,2 CTD (catechol dioxygenase) sequences clearly showed an evolutionary relationship between 1,2 dioxygenases of both Halomonadaceae and Pseudomonadaceae . In comparison, 2,3 CTD of Marinobacter HA2 shared the main domains of the closely related species. Furthermore, semi-quantitative RT-PCR analysis proved the constitutive expression pattern of both dioxygenase genes. These findings provide new isolates of Halomonas sp. and Marinobacter sp. that can degrade phenol at high salt and pH conditions via two independent mechanisms.

Model Synthetic Samples for Validation of NMR Signal Simulations - Nicholas N. A. Ling; Syed Rizwanullah Hussaini; Mahmoud Elsayed; Paul R. J. Connolly; Ammar El-Husseiny; Mohamed Mahmoud; Eric F. May; Michael L. Johns (Transport in Porous Media, 2022)
Simulations of nuclear magnetic resonance (NMR) signal from fluids contained in porous media (such as rock cores) need to account for both enhanced surface relaxation and the presence of internal magnetic field gradients due to magnetic susceptibility contrast between the rock matrix and the contained fluid phase. Such simulations are typically focussed on the extraction of the NMR T 2 relaxation distribution which can be related to pore size and indirectly to system permeability. Discrepancies between such NMR signal simulations on digital rock cores and associated experimental measurements are however frequently reported; these are generally attributed to spatial variations in rock matric composition resulting in heterogeneously distributed NMR surface relaxivities (ρ) and internal magnetic field gradients. To this end, a range of synthetic sediments composed of variable mixtures of quartz and garnet sands were studied. These two constituents were selected for the following reasons: they have different densities allowing for ready phase differentiation in 3D μCT images of samples to use as simulation lattices and they have distinctly different ρ and magnetic susceptibility values which allow for a rigorous test of NMR simulations. Here these 3D simulations were used to calculate the distribution of internal magnetic field gradients in the range of samples, these data were then compared against corresponding NMR experimental measurements. Agreement was reasonably good with the largest discrepancy being the simulation predicting weak internal gradients (in the vicinity of the quartz sand for mixed samples) which were not detected experimentally. The suite of 3D μCT images and associated experimental NMR measurements are all publicly available for the development and validation of NMR simulation efforts.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Selenium Nanoparticles Act Potentially on the Growth Performance, Hemato-Biochemical Indices, Antioxidative, and Immune-Related Genes of European Seabass (Dicentrarchus labrax) - Marwa F. Abd El-Kader; Ahmed F. Fath El-Bab; Mohamed F. Abd-Elghany; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Mahmoud A. O. Dawood (Biological Trace Element Research, 2021)

Embryonic thermal manipulation of Japanese quail: effects on embryonic development, hatchability, and post-hatch performance - Saad N. El-Shater; Hamdy Rizk; Hisham A. Abdelrahman; Mohamed A. Awad; Elsayed F. Khalifa; Karim M. Khalil (Tropical Animal Health and Production, 2021)

RETRACTED ARTICLE: COVID-19: pathogenesis, advances in treatment and vaccine development and environmental impact—an updated review - Youssef A. Attia; Mohamed T. El-Saadony; Ayman A. Swelum; Shaza Y.A. Qattan; Adel D. Al-qurashi; Khalid A. Asiry; Manal E. Shafi; Ahmed R. Elbestawy; Ahmed R. Gado; Asmaa F. Khafaga; Elsayed O.S. Hussein; Hani Ba-Awadh; et al. (Environmental Science and Pollution Research, 2021)

Formulation, Pharmacokinetics evaluation, and IVIVC Assessment of Gliclazide Multiparticulates in Rat Model - Ahmed A. El-Ashmawy; Aya R. Abdou; Nesrin F. Taha; Ebtesam W. Elsayed; Khaled M. Mahmoud; Laila H. Emara (AAPS PharmSciTech, 2021)

The utility of electrocardiography and echocardiography in copper deficiency-induced cardiac damage in goats - Ahmed S. Mandour; Roushdy F. Elsayed; Asmaa O. Ali; Ahmed E. Mahmoud; Haney Samir; Amina A. Dessouki; Katsuhiro Matsuura; Izumi Watanabe; Kazuaki Sasaki; Salim Al-Rejaie; Tomohiko Yoshida; Kazumi Shimada; et al. (Environmental Science and Pollution Research, 2021)

Development of activated carbon fibers for removal of organic contaminants - D. S. S. Alkathiri; M. A. Sabri; T. H. Ibrahim; Y. A. ElSayed; F. Jumean (International Journal of Environmental Science and Technology, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Quantitative Tortuosity Measurements of Carbonate Rocks Using Pulsed Field Gradient NMR - Kaishuo Yang; Ming Li; Nicholas N. A. Ling; Eric F. May; Paul R. J. Connolly; Lionel Esteban; Michael B. Clennell; Mohamed Mahmoud; Ammar El-Husseiny; Abdulrauf R. Adebayo; Mahmoud Mohamed Elsayed; Michael L. Johns (Transport in Porous Media, 2019)

Silicon Alleviates Nickel-Induced Oxidative Stress by Regulating Antioxidant Defense and Glyoxalase Systems in Mustard Plants - Elsayed F. Abd_Allah; Abeer Hashem; Pravej Alam; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2019)

Identification of serum N-glycoproteins as a biological correlate underlying chronic stress response in mice - Motamed Elsayed Mahmoud; Ibrahim F. Rehan; Kh. El-Dawy Ahmed; Amany Abdelrahman; Saeed Mohammadi; Ahmed F. Abou-Elnaga; Mohammed Youssef; Hassan Mahmoud Diab; Doaa Salman; Asmaa Elnagar; Hesham H Mohammed; Obeid Shanab; et al. (Molecular Biology Reports, 2019)

Syphacia muris infection in rats attenuates colorectal carcinogenesis through oxidative stress and gene expression alterations. Implications for modulatory effects by Bryostatin-1 - Elsayed I. Salim; Samar F. Harras; Aisha G. Abdalla; Mohmmed H. Mona (Acta Parasitologica, 2018)
Accumulating evidence suggest that some infectious agents may interfere in the natural progression of neoplasia. This study examined the association between chronic infection with adult Syphacia muris parasites and 1,2-dimethylhydrazine (DMH)-induced colorectal carcinogenesis in rats. In addition, the conceivable therapeutic effect of Bryostatin-1, a potent extract of the marine Bryozoan, Bugulane ritina , was investigated against this combined effect.DMH administration has induced aberrant crypt foci (ACF), surrogate biomarkers for colorectal carcinogenesis, while the S . muris infection combined with DMH has significantly increased the total numbers of ACF. Nonetheless, treatment with Bryostatin-1 after infection has significantly reduced the ACF numbers particularly larger ones. This inhibition was concomitant with significant inhibition in the immunohistochemical levels of the ki67, Caspase-3 and IgM levels in colorectal epithelium, as well as serum levels of IgM and IgG. Additionally, treatment with Bryostatin-1 after S . muris + DMH has modulated enzymatic antioxidative markers levels of superoxide dismutase and catalase as well as the non-enzymatic antioxidant markers levels of reduced glutathione, lipid peroxidation, nitric oxide and total antioxidant capacity. Further, treatment with Bryostatin-1 has down-regulated the mRNA expression levels of COX-2 and APC genes in colorectal mucosa. In conclusion, infection with S . muris during colorectal carcinogenesis has significantly modulated the oxidative stress markers in the colorectum, while treatment with Bryostatin-1 has exerted significant curative potential. A mechanism could be explained that Bryostatin-1 treatment has reduced oxidative stress markers activities along with affecting host to parasite immunity possibly leading to changes in the COX-2 and APC expression, retarding cellular proliferation and subsequently reducing the colorectal carcinogenesis events.

Rhamnolipids Enhance in Vivo Oral Bioavailability of Poorly Absorbed Molecules - El-Sayed Khafagy; Mona F. El-Azab; Mohamed E. H. ElSayed (Pharmaceutical Research, 2017)

Epidemiological investigation of Middle East respiratory syndrome coronavirus in dromedary camel farms linked with human infection in Abu Dhabi Emirate, United Arab Emirates - Salama Al Muhairi; Farida Al Hosani; Yassir M. Eltahir; Mariam Al Mulla; Mohammed F. Yusof; Wissam S. Serhan; Farouq M. Hashem; Elsaeid A. Elsayed; Bahaaeldin A. Marzoug; Assem S. Abdelazim (Virus Genes, 2016)

Prevalence of Middle East respiratory syndrome coronavirus (MERS-CoV) in dromedary camels in Abu Dhabi Emirate, United Arab Emirates - Mohammed F. Yusof; Yassir M. Eltahir; Wissam S. Serhan; Farouk M. Hashem; Elsaeid A. Elsayed; Bahaaeldin A. Marzoug; Assem Si Abdelazim; Oum Keltoum A. Bensalah; Salama S. Al Muhairi (Virus Genes, 2015)

Triggering upstream channel incision in the fluvial systems of the trunk valley of Wadi Watir drainage basin, South Sinai Peninsula, Egypt - ElSayed A. Hermas; Mohamed F. Sadek (Arabian Journal of Geosciences, 2013)

Tranilast ameliorates impaired hepatic functions in Schistosoma mansoni-infected mice - Eman Said; Shehta A. Said; Wagdi F. Elkashef; Nariman M. Gameil; Elsayed M. Ammar (Inflammopharmacology, 2012)

Sequencing and Utilization of the Gossypium Genomes - Andrew H. Paterson; Jun-kang Rong; Alan R. Gingle; Peng W. Chee; Elizabeth S. Dennis; Danny Llewellyn; Leon S. Dure; Candace Haigler; Gerald O. Myers; Daniel G. Peterson; Mehboob ur Rahman; Yusuf Zafar; et al. (Tropical Plant Biology, 2010)

Laboratory-based surveillance of patients with bacterial meningitis in Egypt (1998–2004) - S. Afifi; M. O. Wasfy; M. A. Azab; F. G. Youssef; G. Pimentel; T. W. Graham; H. Mansour; N. Elsayed; K. Earhart; R. Hajjeh; F. Mahoney (European Journal of Clinical Microbiology & Infectious Diseases, 2007)